The Effect of Upper Body Weight Training Using Dumbbells on The Speed of Flying Shoots on The Bojonegoro Men's Handball Porprov Team - Asykur, Rifqi Maulana; Widiawati, Prisca (Indonesian Journal of Sport Management, 2024)
This study aims to determine the effect on weigth training upper body using dumbbells on flyng shoot speed on the Bojonegoro handball men's porprov team. The design in this study was a pre- experimental design with the One-Group Pretest-Posttest Design method and a quantitative descriptive research approach. The sample was taken using total sampling where the number of samples used was 13 athletes of the Bojonegoro handball men's porprov team with an average age of  20 years. The research instrument used a ball speed test and for data analysis using Paired simple T-Tes. The study concluded that there was a significant effect on weigth training upper body using dumbbell terhadapat flyng shoot speed on the Bojonegoro handball men's porprov team. thus this training method can be a recommendation to Bojonegoro handball athletes as an alternative to improve physical performance.